2016
DOI: 10.3389/fpsyg.2016.00614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Fragmented View of One’s Partner on Interpersonal Coordination in Dance

Abstract: In this study we investigated the effects of a mirror-mediated, partial view of one’s dance partner on interpersonal coordination in dance duets. Fourteen participant pairs (dyads) were asked to perform a reflectionally-symmetric eight-segment dance-relevant arm movement sequence in two visual conditions: with one dancer facing the mirror and providing a partial view on the dance partner, or both dancers facing back to back with, for both dancers, no view on one’s partner. During an eight-count beat-preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Despite the real possibility of being used simultaneously to study multiple factors impacting body coordination, accelerometers have typically been utilized to inquire into musical features that could affect the emergence of coordinated interpersonal movement patterns in natural and semi-natural contexts. Accelerometers have recently been utilized to study the coordination of people dancing together to the rhythm of music ( Ellamil et al, 2016 ; Lang et al, 2016 ; Tarr et al, 2016 ) or to the rhythm of a metronome ( Brown and Meulenbroek, 2016 ). For example, Ellamil et al (2016) investigated the influence of various musical features on group synchrony.…”
Section: Motion Tracking Methodsmentioning
confidence: 99%
“…Despite the real possibility of being used simultaneously to study multiple factors impacting body coordination, accelerometers have typically been utilized to inquire into musical features that could affect the emergence of coordinated interpersonal movement patterns in natural and semi-natural contexts. Accelerometers have recently been utilized to study the coordination of people dancing together to the rhythm of music ( Ellamil et al, 2016 ; Lang et al, 2016 ; Tarr et al, 2016 ) or to the rhythm of a metronome ( Brown and Meulenbroek, 2016 ). For example, Ellamil et al (2016) investigated the influence of various musical features on group synchrony.…”
Section: Motion Tracking Methodsmentioning
confidence: 99%
“…Early measurements of SMC, through the synchrony field, involved either intensive behavioral coding 26 or behavioral ratings 27 or explicitly manipulating study conditions to promote a narrow definition of synchrony, such as a dyad bouncing or swinging at the same time to a beat. 11,28 Mathematical applications to applied sciences now allow researchers to quantify SMC using both linear (cross-correlations) 5,22,[29][30][31] and nonlinear (i.e., coherence, relative phase, and cross-wavelet analyses) 1,2,6,32 approaches using a variety of different methods for capturing movement activity, including motion sensors, 9 accelerometers, 33,34 and musical instrument digital interface (MIDI)/audio recordings (e.g., to capture moments of contact during a drum hit). 15,35 SMC has also been measured through the timeseries analysis of movement obtained from the frame-difference method (FDM), 29,36,37 which measures the difference in luminance of grayscale pixels between consecutive video frames.…”
Section: General Introductionmentioning
confidence: 99%
“…One limitation of the research studies so far is concerning the elements involved in motor coordination of ballet movements. For instance, only one study has analyzed upper limb movements of classical ballet [51]. Despite accepting a higher relevance of the lower limbs in the performance of ballet movements, upper limbs may also have a significant contribution to increase balance and movement fluidity, as we have found that postural sway plays an important role in motor behavior of ballet movements [28,41,44,52,80,[92][93][94][95].…”
Section: Discussionmentioning
confidence: 83%